Strategi Pengembangan Industri Ukiran Akar Kayu di Desa Pulau Betung Kabupaten Batanghari - Novi Mubyarto; Ani Maryani; Mohammad Orinaldi (Fakultas Ekonomi dan Bisnis Islam UIN STS Jambi, 2020)
This study aims to investigate the development of the Wood Root Carving Industry in Pulau Betung Village, Pemayung District, Batanghari Regency. The data collection techniques in this study are using observation, interview and documentation techniques. The data analysis used is the SWOT analysis. The results show that the obstacles in the development of the Wood Root Carving Industry in Pulau Betung Village are the quality of marketing and the sustainability of production. As for the opportunity factor in the Wood Root Carving Industry is still accepted by the market outside the city, the sale of carvings is still profitable. The craftmans have passion in learning to carve and and how to sell it. It can be concluded that an alternative development strategy that can be done for the development of the Wood Root Carving Industry in Pulau Betung Village, Pemayung District, Batanghari Regency is to take advantage of existing opportunities.